Follow-up endoscopy rates as an indicator of effectiveness in colon capsule endoscopy: a systematic review and meta-analysis - Ian Io Lei; Alexandra Agache; Alexander Robertson; Camilla Thorndal; Ulrik Deding; Ramesh Arasaradnam; Anastasios Koulaouzidis (Clinical Medicine, 2025)
Introduction: Colon capsule endoscopy (CCE) has emerged as a promising alternative for investigating lower gastrointestinal symptoms. However, its adoption has been limited because of concerns about cost-effectiveness, significantly influenced by follow-up endoscopy rates. Understanding CCE's follow-up endoscopy rates is crucial for its integration into routine clinical practice. We synthesised the evidence to evaluate the overall rate of further investigation in CCE. Materials and Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. Electronic databases, including Medline, Embase and PubMed, were searched for studies reporting follow-up endoscopy rates after CCE, including subsequent endoscopic procedures and radiological imaging. There were no language restrictions or limitations in CCE referral indications, patient recruitment criteria or pathologies investigated. A random-effects model was used for meta-analysis and meta-regression to identify key contributing factors. Results and Discussion: 2,850 participants from 19 studies were included in the analysis. Compared with the key performance indicators for follow-up endoscopy rates in colonoscopy (0.10–0.15) and computed tomography (CT) colonography (0.25), the pooled follow-up endoscopy rate for CCE was found to be 0.42 (95% CI: 0.34–0.50). The meta-regression analysis identified complete transit rates and adequate bowel cleansing quality as factors inversely associated with follow-up endoscopy rates. Furthermore, the CCE2 capsule demonstrated a higher reinvestigation risk than CCE1, likely because of its improved diagnostic accuracy. Although CCE indications were associated with lower follow-up endoscopy rates, subgroup analysis did not reach statistical significance with high heterogeneity. Conclusion: This study highlights a significant follow-up endoscopy rate for CCE and identifies key contributing factors, emphasising the importance of appropriate patient selection to reduce reinvestigation needs. Future research should focus on improving completion rates and bowel preparation protocols, and refining CCE indications. This will minimise environmental impact and enhance cost-effectiveness and patient satisfaction.